Mycobacterium avium subsp. paratuberculosis survival during fermentation of soured milk products detected by culture and quantitative real time PCR methods - Klanicova, B; Slana, I; Roubal, P; Pavlik, I; Kralik, P (International journal of food microbiology, 2012)
Mycobacterium avium paratuberculosis (MAP), etiological agent of paratuberculosis in ruminants, is able to survive extreme conditions like very low pH (stomach), high temperature (pasteurization) or low temperature (refrigerated storage). Cheese, infant powder milk, cream and other milk and dairy products might thus be considered as possible sources of MAP for humans. The aim of this study was to investigate the survival of two MAP field isolates during fermentation of three different types of soured milk products (SMP; yogurt, acidophilus milk and kefir) under laboratory conditions. Pasteurized MAP-free milk was artificially contaminated with 10(6)MAPcells/mL and survival and absolute numbers of MAP were monitored during fermentation (4 or 16 h) and after six weeks of storage at 4°C by culture and quantitative real time PCR (qPCR). Viability of MAP was determined by culture using Herrold's egg yolk medium and Middlebrook 7H10 with antibiotics, supplemented with Mycobactin J and incubated at 37°C for up to 12 weeks. The absolute numbers of MAP were quantified by previously published qPCR assays targeting F57 and IS900 loci in MAP genome. We herein confirm that MAP can survive pH reduction, however, longer exposure to pH below 4 in SMP seems to be critical because it inhibits growth. Therefore, it is suggested that probiotic cultures that can decrease pH below 4 during fermentation could provide better inactivation of MAP in SMP.
Keywords: Animals; Probiotics; Real-Time Polymerase Chain Reaction; sýr; Pasteurization; vysoká teplota; Dairy Products; Hot Temperature; fermentace; Cheese; Mycobacterium avium subsp. paratuberculosis; Milk; pasterizace; probiotika; mléčné výrobky; Fermentation; Paratuberculosis; zvířata; mléko; kvantitativní polymerázová řetězová reakce; paratuberkulóza